Lipidome association with vascular disease and inflammation in HIV+ Ugandan children. (1st August 2021) - Dirajlal-Fargo, Sahera; Sattar, Abdus; Yu, Jiao; Albar, Zainab; Chaves, Fabio C.; Riedl, Ken; Kityo, Cissy; Bowman, Emily; McComsey, Grace A.; Funderburg, Nicholas
Abstract : Objective: HIV infection and antiretroviral therapy (ART) have both been linked to dyslipidemia and increased cardiovascular disease (CVD). The relationships among the lipidome, immune activation, and subclinical vascular disease in children with perinatally acquired HIV (PHIV) have not been investigated. Methods: Serum lipid composition, including 13 lipid classes constituting 850 different lipid species were measured by direct infusion-tandem mass spectrometry in samples from 20 ART-treated PHIV and 20 age-matched and sex-matched HIV− Ugandan children. All participants were between 10 and 18 years of age with no other known active infections. PHIVs had HIV-1 RNA level 50 copies/ml or less. In addition, common carotid artery intima--media thickness (IMT), as well as plasma marker of systemic inflammation (hsCRP, IL6, sTNFRa I), monocyte activation (soluble CD14 and CD163), and T-cell activation (expression of CD38 and HLA-DR on CD4 + and CD8 + ) were evaluated. Results: Median age (Q1, Q3) of study participants was 13 years (11, 15), 37% were boys, 75% were on an NNRTI-based ART regimen. The concentrations of cholesterol ester, LCER, phosphatidylcholines, and sphingomyelin lipid classes were significantly increased in serum of PHIV compared with HIV (P⩽0.04). Biomarkers associated with CVD risk including hsCRP, sCD163, and T-cell activation were directly correlated with lipid species in PHIV ( P  ⩽ 0.04). Contents of free fatty acids including palmitic (16 : 0), stearic (18 : 0), and arachidic acid (20 : 0) were positively correlated with IMT in PHIV. Conclusion: Serum lipidome is altered in young virally suppressed PHIV on ART. A direct association between inflammation and lipid species known to be associated with CVD was observed.